Properties of heavy mesons at finite temperature - Gloria Montaña, Angels Ramos, Laura Tolós (SciPost Physics Proceedings, 2020)
We study the properties of heavy mesons using a unitarized approach in a hot pionic medium, based on an effective hadronic theory. The interaction between the heavy mesons and pseudoscalar Goldstone bosons is described by a chiral Lagrangian at next-to-leading order in the chiral expansion and leading order in the heavy-quark mass expansion so as to satisfy heavy-quark spin symmetry. The meson-meson scattering problem in coupled channels with finite-temperature corrections is solved in a self-consistent manner. Our results show that the masses of the ground-state charmed mesons $D(0^-)$ and $D_s(1^-)$ decrease in a pionic environment at $T≠ 0$ and they acquire a substantial width. As a consequence, the behaviour of excited mesonic states (i.e. $D_{s0}^*(2317)^±$ and $D_0^*(2300)^{0,±}$), generated dynamically in our heavy-light molecular model, is also modified at $T≠ 0$. The aim is to test our results against Lattice QCD calculations in the future.